On the correct chemical nomenclature of C3S, tricalcium oxy silicate. (April 2020) - Plank, J.
Abstract: C3 S, the main constituent in Portland cement, incorrectly has been denominated as tricalcium silicate at times when analytical instrumentation did not allow to uncover its actual chemical constitution. Today, we know that it is composed of three building blocks, namely Ca 2+, SiO4 4 − tetrahedra and interspersed oxide anions, O 2 − . Consequently, its scientifically correct designation is tricalcium oxy silicate, and its formula needs to be written as Ca3 O(SiO4 ) when indicating its chemical constitution, while Ca3 SiO5 only represents an empirical or sum formula. The presence of separate O 2 – anions in its structure is responsible for its different hydration behavior and higher basicity (release of Portlandite), as compared to C2 S. Consequently, it is proposed to henceforth exclusively use the scientifically correct designation tricalcium oxy silicate and the formula Ca3 O(SiO4 ). Moreover, it is suggested to abandon the oxide-based abbreviations 3CaO·SiO2, 2CaO·SiO2 and 3CaO·Al2 O3 for the clinker phases as they grossly misrepresent their actual chemical constitution.